Enhanced biomass production, lipid yield and sedimentation efficiency by iron ion. (September 2015) - Che, Raoqiong; Huang, Li; Yu, Xuya
Highlights: FeC6 H5 O7 ⋅NH4 OH were beneficial for biomass production and lipid accumulation. The consumption rate of low concentration of Fe was 100%. Fe 3+ can flocculate microalgae cells. Sedimentation efficiency were enhanced by high concentrations of residual Fe 3+ . Abstract: Effects of Fe 3+ on the biomass production, lipid accumulation of Monoraphidium sp. FXY-10 were investigated. Further residual Fe 3+ in the culture medium on the sedimentation efficiency have been also studied. The biomass and lipid productivity of microalgae exhibited an increasing tendency with the concentrations of iron ion augmenting. 150 μM iron ion added into the culture medium result in highest DCW at 1.42 g L −1 while the maximum lipid productivity of 10.71 mg L −1  d −1 were obtained at 50 μM. The results showed that appropriate concentrations of iron ion was beneficial for biomass production and lipid accumulation but higher concentration of that will be more in favor of the sedimentation efficiency of Monoraphidium sp. FXY-10.